Mapping Religious Activities and Pluralities in Houses: Case Study at Balun Village Lamongan - Agus Subaqin; Antariksa Sudikno; Lisa Dwi Wulandari; Herry Santoso (el Harakah: Jurnal Budaya Islam, 2023)
Religious activities are basic things that are indispensable in life and are primary needs that must be met. Religious plurality is a social reality in life; it is a challenge to create religious harmony, but on the other hand, it is prone to conflict. The study aims to map religious activities in the settlement of religious plurality, namely Islam, Christianity, and Hinduism, in Balun village, Lamongan. It applied an environment behavior study approach with a place-centered mapping method to find individuals or groups using and accommodating their behavior in a certain time and space, with aspects studied, namely religious activities, space, and time. Data were obtained from direct observation and interviews with purposive, systematic samples. The results showed that religious activities at home with religious plurality were mapped into two categories: the religious activities of individuals or groups according to their religion; and the religious activities by inviting citizens to their religion and different religions. Mapping of space use showed that the use of semi-public and public space in the home for religious activities result in flexibility in spatial functions and changes in sacred-profane spatial boundaries. The research contributed to the theoretical development of using shared space in the home and creating a space of tolerance in Balun village's religious life. Kegiatan keagamaan merupakan hal mendasar yang sangat diperlukan dalam kehidupan dan menjadi kebutuhan primer yang harus dipenuhi. Pluralitas agama termasuk realitas sosial dalam kehidupan; merupakan tantangan untuk menciptakan kerukunan umat beragama, namun di sisi lain rawan konflik. Kajian ini bertujuan untuk memetakan aktivitas keagamaan dalam penyelesaian pluralitas agama, yaitu Islam, Kristen, dan Hindu, di desa Balun, Lamongan. Penelitian ini menerapkan pendekatan kajian perilaku lingkungan dengan metode place-centered mapping untuk menemukan individu atau kelompok yang menggunakan dan mewadahi perilakunya dalam ruang dan waktu tertentu, dengan aspek yang dikaji yaitu kegiatan keagamaan, ruang, dan waktu. Data diperoleh dari observasi langsung dan wawancara dengan sampel purposif, sistematik. Hasil penelitian menunjukkan bahwa kegiatan keagamaan di hunian dengan pluralitas agama dipetakan menjadi dua kategori yaitu kegiatan keagamaan individu atau kelompok menurut agamanya; dan kegiatan keagamaan dengan mengajak warga untuk beragama dan berbeda agama. Pemetaan pemanfaatan ruang menunjukkan bahwa pemanfaatan ruang semi publik dan publik di rumah untuk kegiatan keagamaan mengakibatkan terjadinya fleksibilitas fungsi ruang dan perubahan batas ruang yang sakral-profan. Penelitian ini berkontribusi pada pengembangan teori pemanfaatan ruang bersama di rumah dan penciptaan ruang toleransi dalam kehidupan beragama di Desa Balun.